Correction: Fluorescence of a chiral pentaphene derivative derived from the hexabenzocoronene Motif. Issue 85 (14th October 2019) - Rietsch, Philipp; Soyka, Jan; Brülls, Steffen; Er, Jasmin; Hoffmann, Katrin; Beerhues, Julia; Sarkar, Biprajit; Resch-Genger, Ute; Eigler, Siegfried
Abstract : Correction for 'Fluorescence of a chiral pentaphene derivative derived from the hexabenzocoronene Motif' by Philipp Rietsch et al., Chem. Commun., 2019, 55, 10515–10518.